Cognitive reserve predicts episodic memory enhancement induced by transcranial direct current stimulation in healthy older adults - Sandrini, Marco; Manenti, Rosa; Gobbi, Elena; Pagnoni, Ilaria; Geviti, Andrea; Alaimo, Cristina; Campana, Elena; Binetti, Giuliano; Cotelli, Maria (Scientific reports, 2024)
Episodic memory shows the largest degree of age-related decline. Anodal transcranial Direct Current Stimulation (tDCS) can enhance episodic memory in aging but there is also evidence of response variability even when using identical stimulation parameters. To explore which inter-individual factors (i.e. age, education, encoding performance, cognitive reserve, tDCS group and timing of tDCS application) may directly and/or indirectly modulate verbal memory recall, we used data from our previous tDCS studies that showed enhanced episodic memory recall in 80 healthy older adults. In these studies we used the same paradigm and stimulation parameters but tDCS was applied during different memory stages. Memory recall was tested 48 hours and 30 days after encoding. Univariate regression models showed that tDCS group (Anodal vs. Sham) predicted memory recall, indicating higher scores in the Anodal group than in the Sham group. Encoding performance predicted memory recall in both tDCS groups. Multiple regression models revealed that cognitive reserve, measured with a life experience questionnaire, predicted memory recall only for the Anodal group. Higher cognitive reserve was linked to better memory recall. Accounting for individual differences in cognitive reserve at baseline helps to explain tDCS responsiveness. This knowledge may contribute to optimize its use in older adults.